2013
DOI: 10.1590/s2317-64312013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Sinais comportamentais dos Transtornos do Déficit de Atenção com Hiperatividade e do Processamento Auditivo: a impressão de profissionais brasileiros

Abstract: Purpose:To characterize the behavioral signs of attention deficit hyperactivity disorder (ADHD) and central auditory processing disorder (CAPD) from the perspective of the professionals who diagnose and manage these conditions in Brazil. Methods: Forty-two health professionals in Brazil (medical doctors, speech therapists, psychologists, and pedagogues) participated in this study, and they responded to a questionnaire listing 58 behavioral signs of ADHD and CAPD. The participants were asked to score the listed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Deficits in the relation between working memory and performance in activities affect the development of phonological awareness and may lead to difficulties in learning to read (2) . It is also worth mentioning the relation between ADHD and auditory processing disorder, which has been discussed in some studies (3,4) . One of the studies that reported the impression of Brazilian professionals on this relationship (4) shows that some behavioral signs are characteristic of ADHD, whereas others are characteristic of auditory processing disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in the relation between working memory and performance in activities affect the development of phonological awareness and may lead to difficulties in learning to read (2) . It is also worth mentioning the relation between ADHD and auditory processing disorder, which has been discussed in some studies (3,4) . One of the studies that reported the impression of Brazilian professionals on this relationship (4) shows that some behavioral signs are characteristic of ADHD, whereas others are characteristic of auditory processing disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning the relation between ADHD and auditory processing disorder, which has been discussed in some studies (3,4) . One of the studies that reported the impression of Brazilian professionals on this relationship (4) shows that some behavioral signs are characteristic of ADHD, whereas others are characteristic of auditory processing disorders. This fact suggests that ADHD and auditory processing disorder possibly occur independently.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as condições clínicas que envolvem distúrbios atencionais podem ser incluídas o traumatismo crânio-encefálico, os distúrbios globais e invasivos do desenvolvimento, o transtorno de déficit de atenção e hiperatividade (TDAH), o transtorno do processamento auditivo, o transtorno de aprendizagem, a anóxia/hipóxia, a exposição pré-natal a toxinas, o transtorno de ansiedade generalizada, a depressão, a esquizofrenia e a bipolaridade (Barbosa, Miranda, & Bueno, 2014;Günther, Konrad, Brito, Herpertz-Dahlmann, & Vloet, 2011;Pereira, Santos, & Feitosa, 2013). …”
Section: 1alterações Dos Mecanismos Atencionais E O Comprometimentunclassified